Assessing the Applicability of Ecological Materials Obtained with CRT Glass. Issue 1 (December 2020) - Dumitru, Florina-Diana; Moncea, Mihaela-Andreea; Baraitaru, Andreea-Georgiana; Gheorghe, Petrache-Ionut; Stanciu, Silvius; Deák, György; Ahmad, Romisuhani
Abstract: Recovery and recycling of cathode ray tube (CRT) waste glasses has been the focus of research in the last decade, due to their environmental and economie issues (such as leaching of lead ions, high disposal costs). A sustainable method of valorizing this hazardous waste is to embed it in cement, as a substitute for the natural aggregate. Therefore, within the present study, ecological materials with cementitious matrix were synthesized by using glass waste recovered from cathode ray tube monitors (CRT glass), which replaced the aggregate in different proportions (varying from 10 to 30%), and by substituting 25% of cement with lime paste. The compression strength of the obtained specimens was determined after 1, 2, 7 and 28 days of hardening and highlighted that the samples with lower CRT glass substitution percentage performed relatively similar to the reference sample. This behavior can be explained by scanning electron microscopy (SEM) coupled with energy dispersive X-ray spectroscopy (EDS). The samples microstructure revealed the presence of ettringite, calcium hydroxides, hydrosilicates and hydroaluminates, calcite and some unreacted particles. The opportunity of using these materials in practical applications was assessed by developing masonry specimens - the obtained mortar paste was interposed between two brick slabs, which were mechanically tested after 7 days of hardening. Both splitting tensile strength and flexural strength varied with the increase of CRT glass in the composition.